Pengaruh Brand Activism, Persepsi Konsumen Terhadap Loyalitas Merek: Analisis dalam Konteks Industri Fast Fashion di Jawa Barat - Budi Utomo, Sulistyo; Utami, Eva Yuniarti; Ardhiyansyah, Andri (Universitas Nusa Putra, 2023)
This study investigates the dynamics between brand activism, consumer perceptions, and brand loyalty in the fast fashion industry in West Java. A diverse sample of 250 consumers provided insights into their perceptions and preferences. The study revealed that most respondents had positive perceptions of brand activism initiatives by fast fashion brands, highlighting its resonance with West Java consumers. Regression analysis confirmed a significant positive relationship between consumer perceptions of brand activism and brand loyalty. This research contributes to understanding the impact of brand activism and underscores its potential to drive brand loyalty in culturally diverse markets.